Elemental geochemistry of lower Silurian Longmaxi shale in southeast Sichuan Basin, South China: Constraints for Paleoenvironment. (4th July 2017) - Han, Shuangbiao; Zhang, Jinchuan; Wang, Chengshan; Tang, Xuan
Abstract : A significant proportion of shale gas resources occurs in Lower Silurian Longmaxi Formation in southeast Sichuan Basin, South China, where commercial gas production has been achieved at Fuling Shale Gas Field. This study area is located adjacent to Fuling Jiaoshiba shale play. Elemental geochemistry regarding paleoenvironment aspects of lower Silurian Longmaxi shale gas is poorly understood. However, the samples in this study are representative, revealing the complete elemental geochemical characteristics of Longmaxi Shale. This research has analysed trace and rare earth elements of lower Silurian Longmaxi Shale and investigated the depositional environment, provenance, and tectonic settings when this type of shale formed. Sedimentary structures include horizontal lamination, massive lamination, and deformation structures that are well developed in black shale and grey silty shale of lower Silurian Longmaxi Formation. Gamma ray, total organic carbon, and pyrite contents are relatively higher in the lower part of the shale. The enrichment of sulfophile heavy metal elements (Cu, Zn, Pb, Mo, Ni) indicates that a reducing environment is common during the deposition of Longmaxi Formation. The concentration of rare earth elements is generally constant with relatively high concentration of light rare earth elements, stable concentration of heavy rare earth elements, and negative Eu anomalies. The sediments of Longmaxi Formation are derived primarily from the sedimentary rocks and granites in continental crust. The combination of trace and rare earth elements indicates that the tectonic settings of the provenance are continental island arc and active continental margin.